2014
DOI: 10.1002/anie.201405758
|View full text |Cite
|
Sign up to set email alerts
|

A Trifluorinated Thiazoline Scaffold Leading to Pro‐apoptotic Agents Targeting Prohibitins

Abstract: A new class of small molecules, with an unprecedented trifluorothiazoline scaffold, were synthesized and their pro-apoptotic activity was evaluated. With an EC50 in the low micromolar range, these compounds proved to be potent inducers of apoptosis in a broad spectrum of tumor cell lines, regardless of the functional status of p53. Fast structure-activity relationship studies allowed the preparation of the strongest apoptosis-inducing candidate. Using a high performance affinity purification approach, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…We previously reported that fluorizoline (Figure 1a ) binds specifically to PHB1 and PHB2 [ 2 ]. To examine whether the pro-apoptotic effects of this compound require PHBs, we sought to analyze the response of PHB-deficient cells to fluorizoline treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that fluorizoline (Figure 1a ) binds specifically to PHB1 and PHB2 [ 2 ]. To examine whether the pro-apoptotic effects of this compound require PHBs, we sought to analyze the response of PHB-deficient cells to fluorizoline treatment.…”
Section: Resultsmentioning
confidence: 99%
“…As apoptosis induction can affect ΔΨm [ 39 ], it was important to analyze ΔΨm before the onset of cell death. To this end, we used Jurkat cells, as previous results from our group showed that cytochrome c was released from mitochondria after 8 h of fluorizoline treatment [ 2 ]. Interestingly, 8 h of fluorizoline treatment resulted only in a slight loss of ΔΨm ( Supplementary Figure 5 ), which suggests that it is a consequence of apoptosis induction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prohibitins have been shown to accumulate in response to several stresses, including chemotherapeutic agents, the UPR ER inducer tunicamycin and nutrient starvation, while PHB knock-down sensitized melanoma cells [116]. Several reports suggest PHB proteins as potential druggable targets to halt cancer proliferation and metastasis, while small molecules exhibiting antitumor effects have been shown to target prohibitins [117,118].…”
Section: The Phb Complex Responds To Mitochondrial Stressmentioning
confidence: 99%